Affective Dissent - Stephen Healy (Cosmopolitan Civil Societies: An Interdisciplinary Journal, 2013)
This article identifies a form of affective bio-politics more intimate, engrained and corporeally enacted than that identified in recent work emphasising the affective qualities of activism and labour. While these latter reinforce and bolster existing analyses through the identification of further affective concerns, affective bio-politics suggests that neoliberalism supports and sustains itself quite fundamentally through, what have generally been, unrecognised affective means. While such affective regulation can only ever be partial and imprecise its unrecognised, and thus implicitly concealed, character lends it a particular cogency. Illuminating the mechanisms through which such affective regulatory modulation is achieved thus has a powerful potential to clarify further opportunities to disrupt and counter neoliberalism. This account juxtaposes an analysis of affective bio-politics with existing analyses of the affective, and performative, dimensions to activist politics, in order to facilitate the identification of specific opportunities for further affective contestationary strategies.